Pelayanan Kesehatan Umroh Provinsi Jawa Barat - Agustina, Agustina; Umar, Ahmad Farid (Jurnal Persada Husada Indonesia, 2021)
Religious tourism today is a very important segment in international tourism and for the last 5 years. Umrah which is categorized as religious tourism does not yet have a clear legal umbrella as for the pilgrimage in Indonesia, there is only the Minister of Religion Regulation Number 18 of 2015 concerning the Implementation of Umrah Worship Trips (PPIU). This study aims to obtain an overview of the implementation of the umrah health service model in West Java. The design of this research is action research with cross sectional data collection on the umrah health service model. This research is collaborative and involves 17 participants who are involved in the implementation of umrah health services in the city of Bandung. Data analysis was carried out qualitatively, using the method of analyzing performance and individual experience as well as institutional behavior, namely through focus group discussions, interviews and questionnaires. The research variables are: Respondents, health facilities, and umrah pilgrims surveillance system. The results showed that in general, the number of health problems in the practice of organizing umrah can be seen from the aspects of health development, health services and health protection. In the umrah health service in the City of Bandung, the role of the PTM Posbindu is very large in providing health services and guidance to umrah pilgrims.